The Determinants for Policy Implementation: A Study of Public Service Mall Program in Indonesia - Putra, Fadillah; Wike, Wike; Nurani, Farida; Ulum, Mochamad Chazienul; Salsabilla, Sekar Aqila; Ferdhianzah, Hefry Johan (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
Research on policy implementation altered from building meta-theory towards explaining concerted action across institutional boundaries, the diversity of actors, loci, and levels. Current theory about factors determining the success of public policy implementation includes managerial, organisational, resources, bureaucracy, and politics. The establishment of Public Service Malls (PSM) in Indonesia is used as a case study to carry out this assessment because it represents a considerable challenge in the implementation process. This study aims to provide new perspectives about the determinants of successful public policy implementation, especially in a highly diverse political context such as Indonesia. This policy implementation involves several ministries at the central level and 540 local governments. This study uses an exploratory qualitative approach, and the data was collected through FGDs and in-depth interviews conducted with relevant ministries and local governments. The data is then analysed using NVIVO to find the structure of the concepts and themes according to the conceptual framework used. This research suggests that factors in policy implementation should be placed in a hierarchical order because they are determinants that cause other factors to emerge. In the case of implementing the PSM policy in Indonesia, the political factor becomes the determining factor, which is the highest position, followed by the bureaucracy, managerial, resources, and the organisational at the end